SP-344 Updates in health surveillance programmes for work-related musculoskeletal disorders. (14th March 2023) - Sharan, Deepak; Colombini, Daniela
Abstract : Work-related musculoskeletal disorders (WRMSD) are the commonest occupational health conditions and impact medical costs, work productivity, work disability, and absenteeism. Occupational physicians and company doctors must conduct health surveillance programmes to prevent WRMSDs in individual workers and working populations. This includes preventative medical examinations to screen for conditions incompatible with the job the worker has been assigned and periodic medical examinations to monitor the worker's health regularly. The Nordic Questionnaire is the most widely used tool, describing WRMSDs that have occurred in the previous 12 months, but it does not include a severity threshold. Existing tools rarely indicate significant differences in WRMSDs between exposed and unexposed workers creating limitations in interpreting the risk-damage relation. Periodic health surveillance for WRMSD is organised on three levels – level 1: programmes address all exposed workers and pick up "anamnestic cases"; level 2: clinical examination of workers who test positive in the anamnestic examination; level 3: instrumental exams (X-rays, ultrasonography, electromyography, etc.) to determine diagnoses. This presentation will discuss the principles of health surveillance programmes for WRMSDs, the limitations of the conventional approaches, and the new software-based Latin Questionnaire (LQ) to be used in the first level of health surveillance. LQ offers a global anamnestic investigation of WRMSD, with a filtering tool (severity threshold) for deciding which workers require the subsequent steps in the health surveillance process (clinical and instrumental testing). LQ is a preliminary epidemiological investigation tool for recording the initial collective impact (already in the anamnestic phase) on the health of workers exposed to occupational biomechanical overload versus unexposed workers. LQ classifies the workers analysed as "positive anamnestic cases", "minor disorder cases", or definitively "negative cases". The LQ software can help conduct preliminary epidemiological studies, processing the collective results of health surveillance activities, at first, purely anamnestic level.